Efforts To Increase Interest In Learning Machine Prime Mover Boats Students Through Learning Method Demonstration In Class X Smk Negeri 1 Sutera Sutera District Of School Year 2015/2016 - Yulhendri Yulhendri (Jurnal Ilmiah Pendidikan Scholastic, 2017)
Basic education is education that underlies secondary education. Shaped elementary education elementary school (SD) and High School (SMP) and secondary education is a continuation of primary education, secondary education consists of general and vocational education. Shaped secondary education schools (SMA) and Vocational High School (SMK). Higher education is an education after secondary education includes educational programs diploma, bachelor's, master's, specialist, and doctoral organized by the college. " Does the application of machine learning methods of demonstration of interest in Prime Mover Boat class X in SMK 1 Silk can be improved ..? " Implementation of Class Action Research conducted at SMK Negeri 1 Sutera . This research was motivated by the location of the school affordable. This study is a Class Action Research with a total time of study 2 months from the month from September to October in Odd Semester Academic Year 201 5 stars / 201 6 . This study was planned to consist of two cycles, which aims to improve the activity and learning outcomes Prime Mover Engineering Ship class X SMK 1 Sutera in the second semester of the academic year 2015-2016. Subject of research is all class X SMK Negeri 1 Sutera 's 27 people in the first semester of the academic year 201 5 stars / 201 6 . Source Data in the study were students of class X SMK 1 Sutera . As for how to capture data that is done in this study are as follows. Data on students' learning activities implemented actions taken when using the observation sheet. In the charging process observation sheets, all indicators of activity was observed contained therein. The observed circumstances are activities in the learning process. Data on study results taken from tests of learning outcomes at each end of the cycle consists of six items about. Motor 2 TAK; Each piston-step process is required 2x, 1x crankshaft rotation while the piston between two steps, just one step affords effort. In size and the same rotation, the motor 2 TAK can produce more power than the motor 4 TAK. The piston and cylinder wall temperature is rather high. Easy to administer and sound quiet bike. Construction is simple because it does not require the intake valve / exhaust. Filling / flushing and incomplete combustion. Rinse pump usage, add gear motor becomes expensive. Used if required a great power and a simple construction.